THE IMPACT OF DEVELOPING EMOTIONAL INTELLIGENCE ON SOCIAL ADAPTATION AMONG SCHOOL STUDENTS (INTERNATIONAL CONFERENCE ON MODERN DEVELOPMENT OF PEDAGOGY AND LINGUISTICS, 2026)
In contemporary educational psychology, emotional intelligence has become one of the most significant factors influencing students’ social adaptation, academic success, and psychological well-being. The increasing complexity of social interaction, rapid technological development, and changing educational environments require students not only to possess cognitive abilities but also strong emotional and interpersonal competencies. This article examines the impact of emotional intelligence development on the social adaptation of school students. The study analyzes theoretical approaches to emotional intelligence, psychological mechanisms of social adaptation, and the role of schools, families, and peer relationships in fostering emotional competencies among children and adolescents. The article also explores the perspectives of major scholars such as Daniel Goleman, John D. Mayer, Peter Salovey, and Lev Vygotsky regarding emotional development and social behavior. The findings indicate that students with higher levels of emotional intelligence demonstrate stronger communication skills, greater empathy, improved conflict resolution abilities, and better adaptation to school and social environments. Furthermore, emotional intelligence contributes significantly to reducing behavioral problems, anxiety, and social isolation among school-aged children.